Characteristics and Consequences of Red Bed Bleaching by Hydrocarbon Migration: A Natural Example From the Entrada Sandstone, Southern Utah. (23rd August 2022) - Bailey, Lydia R.; Drake, Henrik; Whitehouse, Martin J.; Reiners, Peter W.
Abstract: Extensive regions of yellow and white ("bleached") sandstones within the terrestrial Jurassic red bed deposits of the Colorado Plateau reflect widespread interaction with subsurface reduced fluids which resulted in the dissolution of iron‐oxide grain coatings. Reduced fluids such as hydrocarbons, CO2, and organic acids have been proposed as bleaching agents. In this study, we characterize an altered section of the Slick Rock member of the Jurassic Entrada Sandstone that exposes bleached sandstone with bitumen‐saturated pore spaces. We observe differences in texture, porosity, mineralogy, and geochemistry between red, pink, yellow, and gray facies. In the bleached yellow facies we observe quartz overgrowths, partially dissolved K‐feldspar, calcite cement, fine‐grained illite, TiO2 ‐minerals, and pyrite concretions. Clay mineral content is highest at the margins of the bleached section. Fe2 O3 concentrations are reduced up to 3× from the red to gray facies but enriched up to 50× in iron‐oxide concretions. Metals such as Zn, Pb, and rare‐earth elements are significantly enriched in the concretions. Supported by a batch geochemical model, we conclude the interaction of red sandstones with reduced hydrocarbon‐bearing fluids caused iron‐oxide and K‐feldspar dissolution, and precipitation of quartz, calcite, clay, and pyrite. Localized redistribution of iron into concretions can account for most of the iron removed during bleaching. Pyrite and carbonate stable isotopic data suggest the hydrocarbons were sourced from the Pennsylvanian Paradox Formation. Bitumen in pore spaces and pyrite precipitation formed a reductant trap required to produce Cu, U, and V enrichment in all altered facies by younger, oxidized saline brines. Plain Language Summary: Thin coatings of iron‐oxide on grains give sandstones deposited during the Jurassic Period on the Colorado Plateau a characteristic red pigment. Vast areas of yellow and white ("bleached") colored sandstones within these red bed deposits represent widespread interaction with fluids such as hydrocarbons, carbon dioxide, and organic acids, which dissolved the iron‐oxide grain coatings. These altered sandstones can provide useful information on hydrocarbons or carbon dioxide plume migration pathways, relevant to long‐term geological storage of carbon dioxide. In this study, we characterize a section of the Jurassic Entrada Sandstone that exposes a bleached sandstone with hydrocarbon‐saturated pore spaces. By comparing the unaltered red sandstones to the bleached sandstones at the study site, we find that hydrocarbon‐bearing fluids dissolved minerals like iron‐oxide and K‐feldspar, and precipitated minerals such as quartz, calcite, clay, and pyrite. The iron that was dissolved has been locally redistributed into small, dense spherical accumulations (concretions) of pyrite and iron‐oxide. These accumulations also contain significant enrichment of other metals such as lead, zinc, and rare‐earth elements compared to the sandstones. The presence of pyrite and hydrocarbons caused enrichment of copper, uranium, and vanadium in all altered sandstone and concretions compared to the unaltered red sandstone by the later flow of oxidized saline brines. Key Points: The studied bleached section of Jurassic sandstones in the Paradox Basin reflects interaction with migrating hydrocarbons Abundant bitumen supports reduction by hydrocarbons that redistributed iron and high‐field strength elements into localized concretions Compositional and mineralogic gradients across the bleached sandstone compare well with a batch geochemical model of hydrocarbon migration